2006
DOI: 10.1597/05-174
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Palate in Kabuki Syndrome: A Report of Six Cases

Abstract: Kabuki syndrome is a syndrome of rare congenital anomalies that was named after its characteristic appearance, a face resembling that of an actor in a Kabuki play. Although cleft palate is a feature that is sometimes observed in patients with Kabuki syndrome, there are few clinical reports of cleft palate associated with Kabuki syndrome. This report presents six cases of Kabuki syndrome with cleft palate and reviews their clinical features. Our results suggest that (1) patients with cleft palate in Kabuki synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Specifically, the involvement of cranial nerves I, VII, VIII, IX, and/or X are frequently observed in patients with CHARGE syndrome ( Blake et al, 2008 ). The current case presented with right facial nerve palsy, which occurs in 32–50% of patients with CHARGE syndrome ( Blake et al, 2008 ), but has only been reported in one previous study of a patient with KS ( Iida et al, 2006 ). Choanal atresia is another typical symptom identified in 50–60% of patients with CHARGE syndrome ( Blake et al, 1998 ).…”
Section: Discussionmentioning
confidence: 62%
“…Specifically, the involvement of cranial nerves I, VII, VIII, IX, and/or X are frequently observed in patients with CHARGE syndrome ( Blake et al, 2008 ). The current case presented with right facial nerve palsy, which occurs in 32–50% of patients with CHARGE syndrome ( Blake et al, 2008 ), but has only been reported in one previous study of a patient with KS ( Iida et al, 2006 ). Choanal atresia is another typical symptom identified in 50–60% of patients with CHARGE syndrome ( Blake et al, 1998 ).…”
Section: Discussionmentioning
confidence: 62%
“…Cleft lip/palate has been reported with a variable frequency between 12% and 50% of patients . The clefts are mostly isolated palatal or submucous, while combined cleft lip/palate and isolated cleft lip are rare . Dentition abnormalities, including widely spaced teeth and/or hypodontia, have been frequently reported (53–100%) .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Whether or not craniosynostosis is more frequent in KS patients than in the general population remains unclear. So far, it has rarely been described in patients with KS but it might be underreported. We have observed a metopic craniosynostosis in 2 of 42 patients with KMT2D mutation (not reported in our previous study).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…1BD). Additionally, palate and middle ear structures are derived from pharyngeal arches and are affected in KS patients, serving as diagnostic features for the syndrome (2,(4)(5)(6). Zebrafish anterior neurocranium and lower jaw structures are well established models for mammal palate and middle ear development, respectively (33).…”
Section: Kmt2d Zy59 Mutants Exhibit Anomalous Palate Development and mentioning
confidence: 99%